Adult listeners can extract age-related cues from child-directed speech. Issue 12 (December 2022) - Bozkurt, Ceren; Soley, Gaye
This study investigated adult listeners' ability to detect age-related cues in child-directed speech (CDS). Participants ( N  = 186) listened to two speech recordings directed at children between the ages of 6 and 44 months and guessed which had addressed a younger or an older child. The recordings came from North American English-speaking mothers and listeners were native speakers of Turkish with varying degrees of English knowledge. Participants were randomly assigned to listen either to the original recordings or to the low-pass filtered versions. Accuracy was above chance level across all groups. Participants' English level, age, and the age difference between the addressees significantly predicted accuracy. After controlling for these variables, we found a significant effect of condition. Participants' accuracy tended to be better in the unfiltered condition with the exception of male participants without children. These results suggest that age-related variations in CDS are perceptually available to adult listeners. Furthermore, even though sensitivity to the age-related cues is facilitated by the availability of content-related cues in speech, it does not seem to be solely dependent on these cues, providing further support for the form–function relations in CDS.